Development of paddy precision planter for system of rice intensification - Abdulkadir, Tukur Daiyabu (2015)
High labor demand especially at the seedling establishment stage is one of the major challenges faced by paddy farmers in adopting the system of rice intensification (SRI). In this research Gaspardo pneumatic seeder SPS540 was modified and adopted to the direct seeding of coated paddy for the system of rice intensification (SRI), with the aim of solving the drudgery faced by farmers in adopting the SRI. Paddy seeds were fed in to starch and gelatin capsule at the ratio of 1:1 with the capsule serving as paddy coating material to achieve a uniform planting material for single seed planting requirement of the system of rice intensification. Germination analysis for the capsulated seed was conducted in a preliminary study where a germination rate of 92% was achieved with starch capsule coated pre germinated paddy seed. Lower germination rate of 16% was recorded for the case of gelatin capsulated pre germinated paddy. Second round of germination test was conducted using starch capsule, with three treatments of primed coated seed, pre germinated coated seed, and untreated uncoated (control) paddy seed. The highest germination count of 95% was observed with pre germinated coated paddy, followed by primed coated paddy 83%, and the lowest germination count 58% was observed in the control. Solubility of both gelatin and starch capsule in water were compared. Starch capsule was found to have higher solubility at lower temperature corresponding to the paddy environment temperature. The physical, mechanical and aerodynamic properties of the capsulated paddy seed was determined based on which two seed plates designs suitable for capsulated paddy planting were designed and fabricated. One of the designs has 0o entry angle, while the second has 120o entry angle. An electro mechanical seed spacing and metering system was developed from a metering wheel, encoder, servo motor, and arduino micro controller to replace the existing mechanical seed spacing and metering system for improved machine performance. The limit switch (encoder) and the servo motor were programmed using Arduino microcontroller for seed metering. At each designated distance the limit switch will actuate the servo motor to rotate and drop a single seed. The machine was calibrated at the laboratory and performance evaluation of the machine conducted there based on average seed spacing, miss index, multiple index, and quality of feed index. The best performance indices of 25.4 cm average seed spacing, 0% miss index, 0% multiple index, and 100% quality of feed index was observed with zero entry angle seed plate at operational parameters of 10 mbar and 1 m/s. The machine was then evaluated in the field using same performance indices as in the laboratory evaluation. At the field, comparison between the conventional (mechanical) seed metering system and the developed electronic system was made using T test. The T test result proved electronic seed metering system with 32.90 cm seed spacing, 96.30% quality of feed index, 3.7% miss index, and 0% multiple index to be better than the mechanical seed metering system with 21.53 cm average seed spacing, 76.19% quality of feed index, 7.22% miss index, and 16.59% multiple index.